2018
DOI: 10.1002/ijgo.12441
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and unmet sexual and reproductive health needs among international migrant sex workers at the Mexico–Guatemala border

Abstract: There is a crucial need to avoid prioritizing vertical disease-specific services and to promote access to rights-based SRH services for migrant sex workers in both home and destination settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 14 publications
(49 reference statements)
0
63
0
2
Order By: Relevance
“…Isolation, sex work stigma, and socio-cultural stigmas surrounding sex contribute to privacy concerns when it comes to accessing health services and shape the preference of many im/migrant sex workers to neither disclose sex work involvement to their primary care provider nor to access sexual health testing from them [35,36,42,63]. As asserted by our focus group participants and im/migrant sex workers in diverse countries, stigma and fear of poor treatment or discrimination by health professionals are powerful barriers to im/migrant sex workers' access to health care [36,68,73,77], and further enhance their social exclusion.…”
Section: Went To Ams [Unemployment Institution] Because I'm Not Registered As a Sex Worker So They Don't Have Any Idea That I'm A Sex Wormentioning
confidence: 89%
See 1 more Smart Citation
“…Isolation, sex work stigma, and socio-cultural stigmas surrounding sex contribute to privacy concerns when it comes to accessing health services and shape the preference of many im/migrant sex workers to neither disclose sex work involvement to their primary care provider nor to access sexual health testing from them [35,36,42,63]. As asserted by our focus group participants and im/migrant sex workers in diverse countries, stigma and fear of poor treatment or discrimination by health professionals are powerful barriers to im/migrant sex workers' access to health care [36,68,73,77], and further enhance their social exclusion.…”
Section: Went To Ams [Unemployment Institution] Because I'm Not Registered As a Sex Worker So They Don't Have Any Idea That I'm A Sex Wormentioning
confidence: 89%
“…This results in many im/migrant sex workers deferring testing or treatment until a visit to their home country. Five different studies involving im/migrant sex workers from diverse contexts found that a significant proportion of im/migrants reported accessing sexual, reproductive health, and/or HIV/STI services in their country of origin, due to high costs and privacy concerns around using even free sexual health services in the destination country [44,63,[71][72][73]. This raises concerns regarding delays in access to critical health services.…”
Section: One Time He (Sex Work Studio Owner) Took the Keys From The Door And Told Me That He Will Come Back In 2 Hours To Close The Studimentioning
confidence: 99%
“…Por otra parte, los factores sociales antes mencionados, sumados al temor de los grupos vulnerables a una posible estigmatización, serían motivos para que, personas en situación de vulnerabilidad, evite consultar, provocando un posible subdiagnóstico tanto de TB como de VIH 8,22 . Según el reporte oficial de 2018, a nivel mundial, solo en 13% de todos los casos de TB se confirmó la coinfección por VIH, lo que representaría sólo 46% del número de casos esperados 22 .…”
Section: Discussionunclassified
“…The criminalisation and stigmatisation of sex work influence community perceptions of sex workers, reinforcing stigma and discrimination both in healthcare settings and in day-to-day life [18]. As a result, sex workers are often denied equal access to quality health services and may experience difficulties accessing SRH care across their life course [19][20][21][22][23][24]. Together, these overlapping structural barriers contribute to a lack of targeted services, thus violating the right of sex workers to comprehensive and appropriate SRH care.…”
Section: Structural Determinants Of Sexual and Reproductive Health Access For Sex Workersmentioning
confidence: 99%